2016
DOI: 10.1186/s40621-015-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of an algorithm to identify fall-related injuries and costs in Medicare data

Abstract: BackgroundIdentifying fall-related injuries and costs using healthcare claims data is cost-effective and easier to implement than using medical records or patient self-report to track falls. We developed a comprehensive four-step algorithm for identifying episodes of care for fall-related injuries and associated costs, using fee-for-service Medicare and Medicare Advantage health plan claims data for 2,011 patients from 5 medical groups between 2005 and 2009.MethodsFirst, as a preparatory step, we identified ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 20 publications
(53 reference statements)
0
49
0
Order By: Relevance
“…21 We started with the hospital admission claims and determined a patient had experienced a fall if the admitting or primary diagnosis code fields, or primary external cause code field reported an accidental fall (ICD9-CM external cause codes E880-E888, excluding E887), following an algorithm developed by Kim et al for identifying fall-related injuries in Medicare inpatient claims data. 22 In the years of our data, reporting of external cause codes is high, at about 90 percent for all injury cases (Appendix S1). We linked these claims to MDS assessments using beneficiary identifiers and then applied criteria for each MDS fall-related item to identify an appropriate denominator for reporting ( Figure 1).…”
Section: Identification Of Falls For Mds Reportingmentioning
confidence: 92%
“…21 We started with the hospital admission claims and determined a patient had experienced a fall if the admitting or primary diagnosis code fields, or primary external cause code field reported an accidental fall (ICD9-CM external cause codes E880-E888, excluding E887), following an algorithm developed by Kim et al for identifying fall-related injuries in Medicare inpatient claims data. 22 In the years of our data, reporting of external cause codes is high, at about 90 percent for all injury cases (Appendix S1). We linked these claims to MDS assessments using beneficiary identifiers and then applied criteria for each MDS fall-related item to identify an appropriate denominator for reporting ( Figure 1).…”
Section: Identification Of Falls For Mds Reportingmentioning
confidence: 92%
“… FRIs identified using the adapted UCLA/RAND algorithm (Ganz et al. ; Kim et al ) in which serious FRIs are identified using inpatient (hospital and SNF) ICD‐9 primary diagnoses and external cause of injury codes and outpatient diagnoses and procedural codes. Models were estimated using OLS (expenditure change scores) or logistic regression (persistently high expenditures, controlling for preindex expenditures) with robust standard errors. …”
Section: Resultsmentioning
confidence: 99%
“…; Hoffman et al ; Kim et al. ) refines commonly used FRI identification approaches. Although it is potentially an improvement over prior approaches because it uses a more sensitive and specific approach involving inpatient and outpatient diagnoses/procedures, it needs to be further evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…We examined several published diagnosis code-based definitions of falls 16,17 and selected the approach used by Bohl et al 17 Falls were identified by both ICD-9 codes associated with injuries commonly sustained during fall (800–848, 850–854, and 920–924) or e-codes identifying a fall mechanism (E880, E881, E884, E885, or E888). We chose this broad definition to intentionally bias the study towards the null hypothesis: by selecting a coding-based definition which casts a wide net, additional cases identified via chief complaint data were unlikely to have been picked up by more specific definitions.…”
Section: Methodsmentioning
confidence: 99%
“…In prior studies, diagnosis codes, such as the ICD-9 codes and the injury subcodes, have been used as an identifier of falls in large datasets. 16,17 While this is a standard procedure for many conditions within health services research, it may miss many patients in the ED, where visits for falls may result in other diagnosis codes reflecting the injury sustained such as fractures, contusions, etc. without mention of the mechanism of injury.…”
Section: Introductionmentioning
confidence: 99%